2022
DOI: 10.5230/jgc.2022.22.e16
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes of Pylorus-Preserving Gastrectomy for Early Gastric Cancer: Comparison Between Extracorporeal and Intracorporeal Gastrogastrostomy

Abstract: Purpose This study aimed to compare the surgical and oncological outcomes between totally laparoscopic pylorus-preserving gastrectomy (TLPPG) with intracorporeal anastomosis and laparoscopy-assisted pylorus-preserving gastrectomy (LAPPG) with extracorporeal anastomosis. Materials and Methods A retrospective analysis was performed in 258 patients with cT1N0 gastric cancer who underwent laparoscopic pylorus-preserving gastrectomy using two different anastomosis methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The smaller incision led to less tissue damage compared to conventional laparotomy and laparoscopic-assisted surgery 12) , this will reduce the obstruction caused by adhesion of the stomach or intestines and reduce abdominal pains. As compared to LAPPG, the small incisions required for TLPPG remained uniform in size between patients and were independent of patient factors, leading to a potential advantage for using the technique [13][14][15] . The score of the dyspepsia subscale was also lower than that of the PGSAS group.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller incision led to less tissue damage compared to conventional laparotomy and laparoscopic-assisted surgery 12) , this will reduce the obstruction caused by adhesion of the stomach or intestines and reduce abdominal pains. As compared to LAPPG, the small incisions required for TLPPG remained uniform in size between patients and were independent of patient factors, leading to a potential advantage for using the technique [13][14][15] . The score of the dyspepsia subscale was also lower than that of the PGSAS group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the antrum and proximal remnant stomach twist partially around the anastomosis, and the lesser curvature side was not used for anastomosis[ 15 ]. A retrospective analysis showed no significant difference in proximal margin, the number of lymph nodes, surgical complication and postoperative hospital stay between intracorporeal and extracorporeal anastomosis[ 17 ]. Ohashi et al [ 18 ] reported the “piercing method” to perform intracorporeal end-to-end anastomosis with a linear stapler, but this method is cumbersome and time-consuming.…”
Section: Anastomosis Methodsmentioning
confidence: 99%
“…Operations were performed by 4 experienced surgeons. Surgical procedures for LPPG and LDG were the same as previously reported [ 5 8 ]. The infrapyloric artery and vein, the hepatic branch of the vagus nerve, and the first branch of the right gastric artery were preserved without complete lymph node dissection of station 5.…”
Section: Methodsmentioning
confidence: 99%